Exploring Mediterranean and Arctic Environments as a Novel Source of Bacteria Producing Antibacterial Compounds to be Applied in Aquaculture - Carmen Rizzo; Concetta Gugliandolo; Angelina Lo Giudice (Applied Sciences, 2020)
The need to discover new natural compounds has become urgent as a possible alternative solution to contrast the spread of antibiotic resistance, also in the aquaculture field. Bacterium–bacterium inhibitory activity against bacterial pathogens relevant in aquaculture was evaluated on agar plates for bacteria isolated from cold Arctic (Kongsfjorden, Svalbard Islands; i.e., seawater and sediment samples) and temperate Mediterranean (Lake Faro in Messina and the Straits of Messina, Italy; i.e., brackish water and benthic filter-feeding organisms) environments. Cell-free supernatants (both pure and concentrated 10-fold) were further assayed and, in the case of a positive response, crude extracts were obtained and tested. After the pre-screening procedures, about 30% of the bacterial isolates inhibited the growth of at least one pathogen used as a target. The 10-fold concentrated supernatants of two Arctic Salinibacterium spp. strains and the Mediterranean Bacillus sp. PS62 (associated with the pennatulacean Pteroeides spinosum Ellis, 1764) resulted in being active against P. damselae subsp. piscicida. The crude extracts obtained from Bacillus sp. PS62 also showed inhibitory activity against the same pathogen. Our findings suggest that tested bacteria could represent a novel source of compounds to be applied to overcome pathogenesis in the aquaculture field.